(untitled) (KULT_online, 2009)
This volume documents the work of Collaborative Research Centre 511, "Literature and Anthropology" that took place at the University of Konstanz between 1996 and 2002. Borrowing from the closely related disciplines of social, biological, and cultural anthropology, the research sheds light on the dynamic relationship between literary and anthropological studies. In addition to exploring literary anthropology – which draws conclusions about mankind in general from the corpus of written works – Collaborative Research Centre 511 has also embraced the anthropology of literature, and asks to what extent anthropological elements lay the foundation for literary works. The volume contains 14 chapters by authors whose research backgrounds include english, german, slavic and romance studies, psychology and history, as well as cultural and media studies.